PENGARUH PENGGUNAAN MEDIA AUDIOVISUAL TERHADAP MOTIVASI SISWA BELAJAR PENDIDIKAN AGAMA KRISTEN - Gultom, Budhi Soethardodo (IAKN Tarutung, 2019)
Abstract - The research aim was to determine the positive and significant effect between the use of audiovisual media on the learning motivation of Christian Religious Education of tenth-grade students of SMA Negeri 1 Pahae Julu, North Tapanuli Regency in Academic Year 2018/2019. The research used quantitative descriptive methods. The result of data analysis showed that there was a positive and significant effect between the use of audiovisual media on the learning motivation on tenth-grade students of SMA Negeri 1 Pahae Julu, North Tapanuli Regency in academic year 2018/2019 with a determination coefficient of r2 was 39,56% and significant influence of Fcount=26,13 Ftable=4,08, then H0 was rejected and Ha is accepted.Keywords: Audiovisual Media, Learning Motivation.